Lymph Chylomicron Formation during the Inhibition of Protein Synthesis. STUDIES OF CHYLOMICRON APOPROTEINS - Glickman, R. M.; Kirsch, K. (The Journal of Clinical Investigation, 1973)
The effect of impaired intestinal protein synthesis on chylomicron apoprotein composition was studied in mesenteric lymph fistula rats. Lymph was obtained from animals with impaired protein synthesis given intraperitoneal acetoxycycloheximide (ACH), a potent inhibitor of protein synthesis. Lymph chylomicrons were then isolated by ultracentrifugation and purified on agarose columns. Purified chylomicrons from control and ACH-treated animals were delipidated, and their apoprotein pattern was examined on sodium dodecyl sulfate (SDS) polyacrylamide gels. Because we had previously demonstrated a markedly increased lymph chylomicron size during the inhibition of protein synthesis, it was first necessary to determine whether chylomicron apoprotein composition normally varied with chylomicron size. Chylomicrons of varying sizes were prepared by differential ultracentrifugation, and their apoprotein composition was determined densitometrically on SDS polyacrylamide gels. No significant difference in apoprotein composition was found normally with varying chylomicron size. In contrast, however, chylomicrons from ACH-treated animals showed a 50% decrease in a major apoprotein band with R1 0.67. Other chylomicron apoproteins were not decreased as a result of impaired protein synthesis, suggesting differing rates of synthesis of the various chylomicron apoproteins. In vivo incorporation studies of [3H]leucine into the various apoproteins of lymph chylomicrons demonstrated that this apoprotein (R1 0.67) had the most rapid synthesis rate and suggested that it seemed most affected by impaired intestinal protein synthesis. Immunologic studies indicated that this apoprotein was immunologically related to high-density lipoproteins (HDL) and was present in chylomicrons isolated directly from small intestinal mucosa. These studies demonstrate that impaired intestimal protein synthesis is associated with a deficiency in one of the major chylomicron apoproteins and may in part explain the impaired lipid absorption seen during states of impaired protein synthesis. Images